2014
DOI: 10.1159/000365216
|View full text |Cite
|
Sign up to set email alerts
|

Fahr's Disease Linked to a Novel <b><i>SLC20A2 </i></b>Gene Mutation Manifesting with Dynamic Aphasia

Abstract: Background: Idiopathic basal ganglia calcification (IBGC), also known as Fahr's disease, is a rare disorder characterized by widespread cerebral calcifications, an autosomal dominant pattern of inheritance and clinical and genetic heterogeneity. The recently identified IBGC gene, SLC20A2, encodes for type III sodium-dependent phosphate transporter 2 and its loss-of-function mutations may lead to the regional accumulation of inorganic phosphate in the brain, causing calcium phosphate deposition. Objective: To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…This correlation does not seem absolute. There has been at least one study using [18F] FDG-PET that found areas of cortical hypometabolism, in the areas that did not have calcifications or other morphological changes and this correlated to the patient's neuropsychological symptoms [29]. It is therefore plausible that calcium deposition may not be the only pathophysiological mechanism in patients with the genetic mutations and highlights the importance of future studies investigating asymptomatic patients.…”
Section: Pseudohypoparathyroidismmentioning
confidence: 99%
“…This correlation does not seem absolute. There has been at least one study using [18F] FDG-PET that found areas of cortical hypometabolism, in the areas that did not have calcifications or other morphological changes and this correlated to the patient's neuropsychological symptoms [29]. It is therefore plausible that calcium deposition may not be the only pathophysiological mechanism in patients with the genetic mutations and highlights the importance of future studies investigating asymptomatic patients.…”
Section: Pseudohypoparathyroidismmentioning
confidence: 99%
“…Five novel variations recently identified by collaborators are also reported; it includes a total of 50 pathogenic variants (six of which are recurrent, one of them intronic): 22 missense, 13 frameshift, 2 deletions, 7 nonsense, and 6 splice site; comprising a de novo mutation and a large (563,256 bp) genomic deletion affecting multiple genes besides SLC20A2 [Wang et al, 2012;Schottlaender et al, 2012;Hsu et al, 2013;Lemos et al, 2013;Nicolas et al, 2013aNicolas et al, , 2013bZhang et al, 2013;Chen et al, 2013;Kasuga et al, 2014, Loughran et al, 2013Baker et al, 2014;Zhu et al, 2014., Yamada et al, 2014Ferreira et al, 2014;Carecchio et al, 2014;Rubino et al, 2014;Brighina et al, 2014;Taglia et al, 2014]. These variants are extremely rare or absent in major databases, such as the Exome Sequencing Project, 1000 Genomes, dbSNP, or HapMap.…”
Section: Pathogenic Variantsmentioning
confidence: 99%
“…His mother was a carrier for the latter. He and his mother were also heterozygous for the common POLG c.3428A>G (p. Glul 143Gly) polymorphism …”
Section: Case Descriptionmentioning
confidence: 99%